Considering linguistic input in a bilingual situation: implications for acquisition. - Jacobson PF; Cairns HS (Language, Speech & Hearing Services in Schools, 2008)
One aspect of linguistic input that may vary in bilingual speech communities is the use of overregularization (e.g., catched ). In an earlier study, typically developing bilingual Spanish/English-speaking children were noted to use overregularizations in an elicited production task, accept these forms in a grammaticality judgment task, and reject standard irregular forms (e.g., caught) at surprising rates in favor of the overregularization (P. F. Jacobson, 2002). Purpose: This study examined the extent to which bilingual adult speakers reported hearing and using overregularized forms. Method: Thirty Spanish/English-speaking adults who worked in settings with bilingual children served as informants. The stimuli included 15 regular and 15 irregular verbs-each as a correct irregular form and as an overregularization (e.g., caught and catched ) or as a correct regular form and as an irregularization (e.g., helped and holp). Employing a modified grammaticality judgment task, the informants were instructed to state whether they heard these forms produced by bilingual adults and whether or not they themselves ever used the forms. Results: Although monolingual English speakers overwhelmingly rejected hearing or using verregularizations, the bilingual adults responded differently. They acknowledged hearing the correct regular and irregular forms in 96% of the instances presented. However, they also reported hearing 62%, and using 20%, of the overregularizations. Discussion: These results prompt speculation regarding possible variation in the nature of linguistic input in the bilingual community and address learnability issues in the acquisition of the English past tense by bilingual children. The challenges facing speech-language pathologists who work with children from bilingual communities are discussed.